Code Generation with the Model Transformation of Visual Behavior Models - Mészáros, Tamás; Levendovszky, Tihamér; Mezei, Gergely (Electronic Communications of the EASST, 2009)
There exist numerous techniques to define the abstract and the concrete syntax of metamodeled languages. However, only a few solutions are available to describe the dynamic behavior (animation) of visual languages. The aim of our research is to provide visual modeling techniques to define the dynamic behavior of the languages. Previously, we have created languages to describe animation. In this paper, we describe how these models can be processed by model transformation techniques. We elaborate the main steps of the transformation and show the details as well. We use graph rewriting-based model transformation, therefore we provide a highly generic solution which can be easily modified, and analyzed with the techniques borrowed from the field of graph rewriting. The termination analysis for the presented method is also provided.